Good Governing Poverty Alleviation Through the PKH Policy - Independent Women's Groups in Poverty Reduction in Batu City (Study at Batu City Social Service) - Maulana, Indah Dwi; Jainuri, Jainuri; Hardini, Hevi Kurnia (Journal of Local Government Issues, 2019)
Good Governing Poverty Alleviation is a poverty reduction program by implementing a model of Good Governance in this context in the Family Hope Program - Independent Women's Group involving actors in the state, society and private sector. Handling the poverty problem of the Batu City Government in accordance with the Good Governance model through a partnership pattern established with the private sector, KPM and Batu City Social Service is expected to be able to create independent women's groups that are able to try to develop their creativity to rise from poverty for themselves and their families .                    This research uses descriptive qualitative method with data collection techniques such as, observation, interviews and documentation and other data that supports this study both primary and secondary. Based on the results of the study of "Good Governing Poverty Alleviation" through PKH Policy - Independent Women's Groups in Poverty Alleviation in Batu City where there are several problem formulations namely Independent Women's Groups in Poverty Alleviation, Implementation and Dynamics of alleviation Good Governing Poverty through PKH Policy - KPM in Poverty Alleviation Women's Empowerment through Independent Women's Groups in Batu City. The results of this study, namely this policy has actually been well-integrated but in the implementation or implementation at the regional level in this case Batu City has not shown an integration model because there is something that has not been realized normative. What is intended is that the Standard Operating Procedure (SOP) has not been regulated in this policy, there are dynamics such as the KPM human resource capacity that is still below the standard so that the policy implementation and private enthusiasm in implementing this policy very, empowering women through KPM is one of the efforts to improve the economy of KPM through a partnership scheme with entrepreneurs in Batu City.